Tropical field assessment in development of dual-pass photovoltaic tray dryer - Noor Iskandar, Abdurrahman (2020)
Renewable Energy (RE) concept and solution are currently being discussed and favoured worldwide due to future energy consumption. A sustainable solution, which is dependent upon sunlight, normally involving energy conversion methods being further researched due to its low efficiency. Drying technology, which utilizes sunlight is known since ancient times, having various techniques through indirect and direct method. The main problem resulted from photovoltaic technology is the electric conversion efficiency is being lowered due to heat trapped in the PV panel, hence, this project will be focused on the utilizing of heat under the same PV for drying purpose. Contribution of this research mainly be positioned on the design, planning and prototype development of a novel and new technology of dual-pass PV tray dryer intended for herbs drying controlled in a closed system. The uniqueness and distinctiveness of the system is that energy is combined to make use of heat energy dissipated under PV panel with heat energy produced by electrical heater, where heat flow controllable by dedicated temperature controller. A prototype is designed and fabricated in a manner having lightweight and portable, structured in aluminium profile, defined and specified dimension in 1.1m (L) x 0.6m (W) x 0.2m (H) with crops holding capacity of 200g (tested using Peppermint leaves), and other herbs depending on crops density and structural form. Equipped with 120W heater, temperature feedback is supplied with the heater control system. Drying temperature can be regulated to temperature around 40ºC. Two tropical assessments were successfully carried out for finding effect of RH and temperature on a dual- passes heating system under the environmental impact factors and justifications were made on the capability and efficiency to harvest heat under PV panel. The dried sample quality is validated via visual means and determined using intensity of dried sample colour. The prototype is able to drain moisture by rate of 45g/hour H20. High chlorophyll content observed in the final sample, and calculated data bringing solar heat collector efficiency (η) is 50%.